Fetal Biometric Assessment and Infant Developmental Prognosis of the Tadalafil Treatment for Fetal Growth Restriction - Makoto Tsuji; Shintaro Maki; Naosuke Enomoto; Kota Okamoto; Asa Kitamura; Shoichi Magawa; Sho Takakura; Masafumi Nii; Kayo Tanaka; Noriko Yodoya; Hiroaki Tanaka; Hirofumi Sawada; et al. (Medicina, 2023)
Background and Objectives: Tadalafil is expected to treat fetal growth restriction (FGR), a risk factor for stillbirth and neonatal morbidity. This study aimed to evaluate the fetal biometric growth pattern of fetuses with FGR treated with tadalafil by ultrasonographic assessment. Materials and Methods: This was a retrospective study. Fifty fetuses diagnosed with FGR and treated by maternal administration of tadalafil and ten controls who received conventional treatment at Mie University Hospital from 2015 to 2019 were assessed. Fetal biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), femur length (FL), and estimated fetal weight (EFW) at the start of treatment and at two weeks and four weeks of treatment were mainly assessed by ultrasound examination. The Wilcoxon signed-rank test was used to assess the measures. The Kyoto Scale of Psychological Development (KSPD) was used to assess the developmental prognosis on tadalafil-treated children at 1.5 years of corrected age (CA) and 3 years old. Results: The median gestational age at the start of treatment was 30 and 31 weeks in the tadalafil and control groups, respectively, and the median gestational age at delivery was 37 weeks in both groups. The Z-score of HC was significantly increased at 4 weeks of treatment (p = 0.005), and the umbilical artery resistance index was significantly decreased (p = 0.049), while no significant difference was observed in the control group. The number of cases with an abnormal score of less than 70 on the KSPD test was 19% for P-M, 8% for C-A, 19% for L-S, and 11% for total area at 1.5 years CA. At 3 years old, the respective scores were 16%, 21%, 16%, and 16%. Conclusions: Tadalafil treatment for FGR may maintain fetal HC growth and infants’ neuro-developmental prognosis.